2022
DOI: 10.1039/d2tb01621d
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-depletion reinforced enzyme catalytic activity for photothermal assisted bacterial killing by hollow mesoporous CuO

Abstract: he emergence and prevalence of drug-resistant bacteria caused by overuse of antibiotics pose new challenges to the treatment of bacterial infections. In this work, the hollow mesoporous CuO nanozymes (HM-CuO...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
(79 reference statements)
0
13
0
Order By: Relevance
“…Brucella (a facultative intracellular bacterium) infection induced macrophage death depends on T4SS secretion activity ( Tian et al., 2020 ). Up-regulated catalytic activity of special protein may help host cell to eliminate bacteria ( Shi et al., 2022 ). From a model of MRSA infection for 24h murine sepsis, blood samples showed the vancomycin treatment down regulated Toll-like receptor signaling pathway and IL-1β production, but not IL-6 and TNF-α production ( Sharma-Kuinkel et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brucella (a facultative intracellular bacterium) infection induced macrophage death depends on T4SS secretion activity ( Tian et al., 2020 ). Up-regulated catalytic activity of special protein may help host cell to eliminate bacteria ( Shi et al., 2022 ). From a model of MRSA infection for 24h murine sepsis, blood samples showed the vancomycin treatment down regulated Toll-like receptor signaling pathway and IL-1β production, but not IL-6 and TNF-α production ( Sharma-Kuinkel et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…2D and E, the photothermal conversion efficiency of 62.7% was calculated for CuRuO X @HA NPs using the previously reported equation, 30 which is higher than that of the single nanozymes. 26,30 This demonstrated that CuRuO X @HA NPs were expected to be ideal photothermal conversion agents with the potential to inhibit bacterial growth through photothermal inhibition.…”
Section: Photothermal Performance Of Curuo X @Ha Npsmentioning
confidence: 99%
“…According to the previous study, copper oxides are considered to have good photothermal characteristics. 26,27 The UV-vis-NIR spectrum of CuRuO X @HA NPs showed a wide range of absorption from the visible to the NIR region (Fig. S6, ESI †).…”
Section: Photothermal Performance Of Curuo X @Ha Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Nanozymes, as a new generation of artificial enzymes, have attracted a lot of attention, showing potential for tumour catalytic therapy because of their heterogeneous enzyme-mimicking a Department of Biomedical Engineering and Department of Pharmaceutical activities, low cost, high stability, tunable specificity, and robust catalytic activity. [18][19][20][21] Notably, the biological activity of natural enzymes is inextricably linked to their spatial structure. Inspired by this finding, the catalytic performance of nanozymes also should be highly dependent on the rational chemical structure design of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%